The impact of balanced fertilizer on paddy growth - Iramaya Nadira Jamel (2012)
A pot experiment was conducted at the Agropark, Universiti Malaysia Kelantan, Jeli during 10 May 2012 to 30 June 2012 to study the effects of different rations of NPK fertilizers on the growth of rice MR253. After filling the pots with soil, the fertilizers were mixed as per specification of the treatments. The treatments were replicated four times in Randomized Complete Block Design (RCBD). The data on the plant height, number of leaves and number of tillers were recorded at the age of 25 days after sowing. From the collected data, it was found that the treatment of N₄₀ P₆₀ K₀ was the best NPK dose at which the tallest plant and the greatest number of number of leaves/plant and tillers/plant were produced.